Complementary and alternative medicine use for constipation: a critical review focusing upon prevalence, type, cost, and users' profile, perception and motivations. Issue 9 (28th June 2016) - Peng, W.; Liang, H.; Sibbritt, D.; Adams, J.
Summary: Objectives: Complementary and alternative medicine (CAM) is increasingly used by those suffering from constipation. This paper reports the first critical integrative review of CAM use for people with constipation focusing upon the prevalence, type and cost of CAM use, as well as CAM users' profile, perception and motivations. Methods: A comprehensive search of international literature was conducted in MEDLINE, Academic Search Complete (EBSCO), and Allied and Complementary Medicine Database (AMED). The search was limited to original research peer‐reviewed English language articles concerning CAM use for constipation published with an abstract and full text between 2005 and 2015. Results: A total of 35 papers met the inclusion criteria and were included in the review. The review shows approximately one in every three people suffering from constipation use CAM with herbal medicine the most commonly used CAM treatment for constipation and a large proportion of CAM use occurring concurrent with or in addition to conventional medical treatments. While early investigation suggests the cost of herbal medicine use in constipation care may be lower than that associated with the use other CAM modalities and conventional medications, this issue requires further research. Conclusions: Although a high percentage of people with constipation using CAM consider these treatments effective, there remains a need for further in‐depth examination of both patient and provider perspectives as well as communication and decision‐making around CAM use for constipation to inform safe, effective and coordinated care for patients with constipation.